Increased elastic modulus of the synovial membrane in a rat ACLT model of osteoarthritis revealed by atomic force microscopy - Dai,Shouqian (2020)
This study aimed to explore changes in nanoscale elastic modulus of the synovium using atomic force microscopy (AFM) in addition to investigate changes in synovial histomorphology and secretory function in osteoarthritis (OA) in a rat anterior cruciate ligament transection (ACLT) model. Sprague-Dawley rats were randomly assigned to sham control and ACLT OA groups. All right knee joints were harvested at 4, 8, or 12 weeks (W) after surgery for histological assessment of cartilage damage and synovitis in both the anterior and posterior capsules. AFM imaging and nanoscale biomechanical testing were conducted to measure the elastic modulus of the synovial collagen fibrils. Immunohistochemistry was used to visualize the expression of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and matrix metalloproteinase-3 (MMP-3) in the synovium. The OA groups exhibited progressive development of disease in the cartilage and synovium. Histopathological scores of the synovium in the OA groups increased gradually. Significant differences were observed between all OA groups except for the posterior 4W group. The synovial fibril arrangement in all OA groups was significantly disordered. The synovial fibrils in all ACLT OA groups at each time point were stiffer than those in the sham controls. OA rats displayed a significantly higher expression of IL-1β and MMP3 in the anterior capsule. In summary, synovial stiffening was closely associated with joint degeneration and might be a factor contributing to synovitis and increased production of proinflammatory mediators. Our data provided insights into the role of synovitis, particularly stiffening of the synovium, in OA pathogenesis.